Voltage‐Induced High‐Efficient In Situ Presodiation Strategy for Sodium Ion Capacitors. Issue 3 (27th January 2020) - Zou, Kangyu; Cai, Peng; Tian, Ye; Li, Jiayang; Liu, Cheng; Zou, Guoqiang; Hou, Hongshuai; Ji, Xiaobo
Abstract: Sodium‐ion capacitors (SICs) have triggered considerable attention due to potential high energy densities under high power densities. The presodiation process of anodes is very important for the construction of high‐performance SICs; however, in the current presodiation method, metallic sodium is utilized as the presodiation agent through the assembling/disassembling of half‐cells, which is very complicated and dangerous, greatly hindering the development of SICs. Herein, a novel voltage‐induced high‐efficient in situ presodiation approach is successfully realized by introducing organic sodium salts as the sodium sources into the cathode. Moreover, the irreversible electrochemical characteristic of organic sodium salts triggered by high voltage could provide sufficient sodium sources for presodiation without any negative effects for further operation of SICs. Significantly, the diversified anodes like carbon and TiO2 are successfully presodiated and the corresponding SICs manifest excellent electrochemical performances. This rational strategy is anticipated to shed light on a potential avenue for greatly simplifying the assembly process of the SICs, which may largely accelerate the commercialization process of SICs. Abstract : A voltage‐induced high‐efficient in situ presodiation strategy is proposed through the introduction of organic sodium salts into cathodes. Thanks to irreversible chemical reactions of organic sodium salts under high voltage, the diversified anodes are successfully presodiated and corresponding sodium ion capacitors (SICs) manifest excellent electrochemical performances, greatly simplifying the assembly process of SICs.